1993
DOI: 10.1182/blood.v82.1.107.bloodjournal821107
|View full text |Cite
|
Sign up to set email alerts
|

The platelet function defect of cardiopulmonary bypass [see comments]

Abstract: The use of cardiopulmonary bypass (CPB) during cardiac surgery is associated with a hemostatic defect, the hallmark of which is a markedly prolonged bleeding time. However, the nature of the putative platelet function defect is controversial. In this study, blood was analyzed at 10 time points before, during, and after CPB. We used a whole-blood flow cytometric assay to study platelet surface glycoproteins in (1) peripheral blood, (2) peripheral blood activated in vitro by either phorbol myristate acetate, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
3
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(129 citation statements)
references
References 64 publications
7
117
3
2
Order By: Relevance
“…CPB causes prolongation of bleeding time and reduced agglutination, secretion and aggregation [13][14][15][16]. Flow cytometric analysis of different platelet receptors reveales no uniform pictures, decreased [13,17,18], unchanged [19] or increased [20] GPIb expression, decreased [18] or unchanged [13,19] GPIIb-IIIa expression, and increased [13] or unchanged [18,19] numbers of activated circulating platelets having been found during ECC. The reasons for these different findings are not clear, but they may be due to different experimental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPB causes prolongation of bleeding time and reduced agglutination, secretion and aggregation [13][14][15][16]. Flow cytometric analysis of different platelet receptors reveales no uniform pictures, decreased [13,17,18], unchanged [19] or increased [20] GPIb expression, decreased [18] or unchanged [13,19] GPIIb-IIIa expression, and increased [13] or unchanged [18,19] numbers of activated circulating platelets having been found during ECC. The reasons for these different findings are not clear, but they may be due to different experimental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…shear stress) or the presence of different subpopulations of circulating platelets. Others have postulated that the platelet functional defect is not an intrinsic defect of the platelet but an extrinsic effect due to lack of availability of platelet agonists caused by heparin-induced inhibition of thrombin [19]. However, there is considerable evidence that not only GPIb but also GPIIb-IIIa is involved in platelet-surface interactions [21].…”
Section: Discussionmentioning
confidence: 99%
“…175 Aprotinin is known to interfere with heparin binding to platelets and appears to reduce peri-and postoperative blood loss resulting from heparin usage. 176,177 Despite the many advantageous effects of aprotinin, results from the BART clinical trial led to suspension of aprotinin's clinical use in May 2008. 178,179 This large multicenter study found that even though the risk of bleeding was lowest in the aprotinin group for patients undergoing high-risk cardiac surgery in comparison to TXA and EACA groups, mortality was significantly higher, which led to early termination of the trial.…”
Section: Natural Kunitz-type Inhibitorsmentioning
confidence: 99%
“…Another cause of coagulopathy is the trauma associated with the extracorporeal circuit resulting in cellular damage. This leads to a decrease in platelet number and function (Kestin et al, 1993) and activation of inflammatory systems. Platelet function is further impaired as a result of hypothermia (Valeri et al, 1987).…”
Section: Cardiac Surgerymentioning
confidence: 99%